Exploring EFL Young Learners in Vocabulary Mastery Based on PPP Approach - Dwi Nopiyadi; Reni Apriani; Amir Hamzah; Iseu Safinatunisa (Journal on Education, 2023)
Mastering vocabulary is one of the important factor in learning English. In general, EFL Young Learners interpret vocabulary as a matter of words and also related to meaning and dictionary. The objectives of this research are: (1) to find out whether or not the use of PPP approach can improve the vocabulary mastery of the fifth grade learners at SD Pasalakan 2 Sumber Cirebon; and (2) to describe the class situation when PPP approach is implemented in teaching vocabulary. The study was carried out by using qualitative and quantitative method. The data collected using various techniques in qualitative method obtain from questionnaire, interview, classroom observation, and field note. While technique of collecting data using quantitative method was obtained from vocabulary test that consist of pre-test and post-test. Then in analyzing the qualitative data, the writer uses analyzing action research, while quantitative data are analyzed by using descriptive statistics method. The improvement of EFL young learners’ vocabulary mastery included: (1) pronouncing words correctly; (2) spelling the words correctly; (3) understanding the meaning of words; (4) making simple English sentences correctly. Related to the improvement in the classroom situation, EFL young learners are more enthusiastic and more interested in learning process.